The Impact of Financial Inclusion on Inflation in the MENA region: Oil vs Non-oil countries - elsaid, jailan (AUC Knowledge Fountain, 2025)
The study examines the impact of financial inclusion on inflation as a tool for monetary policy effectiveness in the MENA region, separating the analysis into oil and non-oil countries from 2004 to 2022. The Principal Component Analysis (PCA) technique is used to create a multidimensional index of financial inclusion through usage and access dimensions. Additionally, PVAR GMM estimation and Granger causality tests are implemented to analyze the dynamics and causality between financial inclusion and inflation, while controlling for other variables such as broad money, real effective exchange rate, and real GDP growth, which may influence the relationship according to the theoretical and empirical literature discussed in this study. The main findings show differences based on regional structure: in oil rich countries, financial inclusion is linked to rising inflation, whereas in non-oil countries, it tends to decrease inflation. The impulse response function (IRFs) results indicate that financial inclusion stabilizes inflation in the long run in oil countries. While, it lowers inflation in the short run in non-oil countries. The conclusion restates that financial inclusion can be an effective tool for monetary policy only in non-oil countries, along with a discussion of the study's limitations and recommendations for further research.